THE EFFECTIVENESS OF USING GROUP INVESTIGATION LEARNING MODELS ON THE SKILLS OF RETURNING ANECDOTE TEXT OF CLASS X STUDENTS OF SMAN 1 LINGGO SARI BAGANTI PESISIR SELATAN - Nurla Warda Malia; Indriani Nisja; Rissa Yulisna (ppjbsip, 2020)
This research is motivated by the lack of skilled students in rewriting anecdote texts, in addition students are still wrong in determining the structure and langunge of anecdoteal texts. This study aims to describe the effetivensesss of the use of the Group Investigation learning model for the re-writing skills of an anecdotes in class X of SMAN 1 Linggo Sari Baganti. This type of research in quantitative research using an experimental model. The design of this study is Posttets-Only Control Design. The population of this study was all students of class x SMAN 1 Linggo Sari Baganti. The sample ini this study was 29th grade students of SMAN 1 Linggo Sari Baganti. The data in the study are the score of anecdote text rewriting skills without using the Group Investigation learning model and the anecdote textrewriting skill score using the Group Investigation learning model of class X students of SMAN 1 Linggo sari Baganti. The results of this study can be concluded as follows. First, the ability to rewrite anecdotal texs in class X students of SMAN 1 Linggo Sari Baganti, South Pesisir Regency without using the Group Investigation model obtained an average value of 73,27 wiht a classification that is more than enough (HC). Secondly, the ability to rewrite anecdotal texts in class X students of SMAN 1 Linggo Sari Baganti, South Coastal District using the Group Investigation model obtained an average rating of 81,03 with a classification that is Good (B). Third, based on the results of the t-test obtained t count>t table 4.70>1.67. So, it can be concluded that the Group Investigation model is effectively used to improve the writing skills of anecdotal text of grade X students of SMAN 1 Linggo Sari Baganti, Pesisir Selatan RegencyAbstrakPenelitian ini dilatarbelakangi oleh kurangnya siswa yang terampil dalam menulis ulang teks anekdot, selain itu siswa masih salah dalam menentukan struktur dan bahasa teks anekdot. Penelitian ini bertujuan untuk mendeskripsikan efektivitas penggunaan model pembelajaran Group Investigation untuk keterampilan menulis ulang anekdot siswa kelas X di SMAN 1 Linggo Sari Baganti. Jenis penelitian dalam penelitian kuantitatif dengan menggunakan model eksperimental. Desain penelitian ini adalah Posttets-Only Control Design. Populasi penelitian ini adalah seluruh siswa kelas x SMAN 1 Linggo Sari Baganti. Sampel dalam penelitian ini adalah siswa kelas 29 SMAN 1 Linggo Sari Baganti. Data dalam penelitian ini adalah skor keterampilan menulis ulang teks anekdot tanpa menggunakan model pembelajaran Group Investigation dan skor keterampilan menulis teks anekdot menggunakan model pembelajaran Group Investigation siswa kelas X SMAN 1 Linggo sari Baganti. Hasil penelitian ini dapat disimpulkan sebagai berikut. Pertama, kemampuan menulis ulang teks anekdot siswa kelas X SMAN 1 Linggo Sari Baganti Kabupaten Pesisir Selatan tanpa menggunakan model Group Investigation diperoleh nilai rata-rata 73,27 dengan klasifikasi yang lebih dari cukup (HC). Kedua, kemampuan menulis ulang teks anekdot siswa kelas X SMAN 1 Linggo Sari Baganti Kabupaten Pesisir Selatan dengan menggunakan model Group Investigation diperoleh nilai rata-rata 81,03 dengan klasifikasi Baik (B). Ketiga, berdasarkan hasil uji-t diperoleh t hitung> t tabel 4,70> 1,67. Sehingga dapat disimpulkan bahwa model Group Investigation efektif digunakan untuk meningkatkan kemampuan menulis teks anekdot siswa kelas X SMAN 1 Linggo Sari Baganti Kabupaten Pesisir Selatan.